Prevalence of sexual harassment among female students at Marondera high school - Majoni, Annie Faith (Midlands State University, 2017)
The purpose of this study was to show the prevalence of sexual harassment of female students at Marondera High School. A Quantitative approach was employed in the study with particular focus on the descriptive survey design which collected data by using a questionnaire. Random stratified sampling was conducted from ZJC , “O” level and “A” level classes. The sample used in the study comprised of sixty (60) female students. Collected data was presented and analyzed through the use of table, graphs and pie charts. The findings of the study established that moderate verbal sexual harassment is prevalent at Marondera High School being perpetrated by male teachers. Participants revealed that they lack comprehensive knowledge of sexual harassment and social constrains were the major reason for not reporting sexual harassment. However, they feel that the school should pursue cases to do with sexual harassment and punish the perpetrators. The researcher recommended policy implementation and adjustment. Sexual harassment should have clear policies that govern the protection of females from being harassed. These policies should state clear lines on appropriate and inappropriate conduct in a student-teacher relationship. Sex education should also be done within the school through clubs and in class such that students are equipped with knowledge and life skills